PEMBERDAYAAN MASYARAKAT NAGARI SILAGO KABUPATEN DHARMASRAYA MELALUI TEKNOLOGI BUDIDAYA TANAMAN KELAPA SAWIT - Zahlul Ikhsan; Yaherwandi Yaherwandi; Siska Efendi; Dewi Rezki; Irwin Mirza Umami; Dede Suhendra (Jurnal Hilirisasi IPTEKS, 2020)
Oil palm plants are the belle of the community in the Dharmasraya Regency today. One of the causes of the low productivity of community plantations is caused by the production technology that is applied relatively simple, starting from seeding to harvesting. With the application of appropriate cultivation technology, it will be directed to increase palm oil production. The activity objectives are to 1) increase the understanding and knowledge of the Nagari Silago community about oil palm production technology, 2) improve the community's knowledge and skills in processing agricultural waste to be more useful 3) encourage the enthusiasm of farmers so that they can better utilize Nagari Silago's agricultural potential. This community service activity was carried out in Nagari Silago District IX Koto Dharmasraya Regency on 26-27 October 2019. This community service activity was carried out using the lecture, discussion method. The number of students involved numbered 150 people. Previously, the community service participants only followed the coconut cultivation technique, which was carried out by the farmers before, even though the cultivation technique was not correct. The Nagari Silago community is very enthusiastic about welcoming and discussing about the technology of oil palm cultivation. Many people ask questions, and good discussions are starting from the origin of seedlings and oil palm nursery techniques, land clearing, fertilizing, castration, pest control, and diseases of oil palm plants. Farmers can consider the concept of 5 T, which is the right way, the proper dosage, the right time, the right type and the right quality that is important in providing that which is not suitable enough for vegetative and generative growth of oil palm.